Validity and reliability of the gender equity scale in nursing education. (10th April 2022) - Cho, Sunhee; Kwon, So‐Hi; Jang, Sun Joo
Abstract: Equity is an emerging issue across all sectors of society, and one of the frequently raised concerns in nursing education is gender inequity. An accurate assessment appears to be a key component in creating an environment of gender equity in nursing education. This study aimed to develop a scale of gender equity in nursing education and establish its validity and reliability. In total, 341 senior nursing students participated in the psychometric evaluation of the Gender Equity Scale in Nursing Education. This psychometric evaluation revealed that the 4‐subdomain (personal experience of gender inequity, perceptions of gender roles, gender discrimination, and gender biases in class), 23‐item measure possesses both good reliability and validity, as well as a good level of internal consistency. The Gender Equity Scale in Nursing Education was developed as a self‐report questionnaire for both female and male students and considers gender role stereotypes, gender‐biased educational climates, gender discrimination, and gender inequity in nursing education.